PENGARUH TRANSFER PEMERINTAH PUSAT DAN FISKAL STRESS TERHADAP BELANJA DAERAH DI PROVINSI PAPUA BARAT - Lillyani Margaretha Orisu; Rumas Alma Yap; Hesty Theresia Salle (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2021)
This research aims to examine the effect of central government transfers, fiscal stress, regional taxes and gross regional domestic product on regional spendingofdistricts/cities in West Papua Province, to analyze the effect of fiscal stress from two indicators, namely the ratio of local revenue to regional spending and the difference in expenditurewith revenue. Using panel data analysis method, the first equation uses a random effect model and the second equation uses a fixed effect model.Finding / Originality: That government transfers and gross regional domestic product have a positive and significant effect on regional spending. By using two measures of fiscal stress, it is found that the fiscal stress variable, both through the ratio of original local income to regional spending, and the difference in expenditures and regional revenues, has a significant and positive effect on regional spending